Pemertahanan Bahasa Jawa Serang pada Fenomena Campur Kode dalam Akun Instagram Influenser Mang Aplen sebagai Kearifan Lokal Masyarakat Kabupaten Serang - Ulinnuha Ulinnuha; Mahpudoh Mahpudoh; Mulya Tiara Fauzi; Julina Julina; Siti Rani; Syamsul Hidayat (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
The waning enthusiasm for preserving the nation's wealth, one of which is regional languages, has become a serious problem that has occurred in recent years. However, only a few Indonesian people are aware of it. Regional languages, especially Serang Javanese, are on the verge of extinction. According to the data obtained, there are three million speakers of Serang Javanese, while the majority of Jaseng (Serang Javanese) speakers are in Cilegon, Serang and a small number in Tangerang, Banten Province. Unfortunately, Banten Javanese language users are starting to be eroded by the progress of the times, people are more in favor of slang communication, South Jakarta language, and the influence of other foreign languages. If the number of speakers decreases from before, it is possible that in the next few years the Jaseng language will experience extinction, which will result in the loss of the local wisdom of the people of Serang district. The good news is that the role of social media, which does not always have a negative impact on society, is actually one of the savior media in preventing the extinction of regional languages. One of them was proven by the owner of an influencer Instagram account from Serang who planned to create content that speaks the Serang Javanese language even though it is part of the code-mixing phenomenon. This research aims to reveal every content with the concept of the code-mixing phenomenon in Mang Aplen's Instagram account in detail, starting from the words, phrases and particles used in the communication. The method used in this research is a descriptive qualitative method which is carried out by analyzing data obtained from speech on Instagram content. The results obtained from this analysis are that there are several single words, phrases, affixes, word repetitions and particles of the Serang Javanese language, dialects and customary activities of the Serang Banten people in the context of entertainment, which are very popular with the community, which reflects the maintenance of the Serang Javanese language. and the local wisdom of the Serang Regency community, this is believed to be able to build community enthusiasm in maintaining the Jaseng language and the local wisdom of the Serang community so that it remains sustainable and strong.